Acrylate polymer

By developing an acrylate polymer with a storage modulus change rate between 2 and 150, the problem of insufficient thermal stability and adhesion of existing adhesives at high temperatures is solved, and the effect of no residual adhesive pollution and low pollution at high temperatures is achieved.

JP2025068622APending Publication Date: 2025-04-28NITTO DENKO SHANGHAI SONGJIANG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024180328
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-16
Filing Date
2024-10-15
Publication Date
2025-04-28

AI Technical Summary

Technical Problem

The existing silicone-based polymer adhesives cause the substrate surface energy to decrease during high-temperature operations, affecting the success rate of wire welding and sealing performance. At the same time, the self-polymerization of the adhesive at high temperatures is insufficient, resulting in residual adhesive contamination.

Method used

An acrylate polymer with excellent high temperature self-polymerization properties is developed, with a storage modulus change rate between 2 and 150, including a soft common domain of 70 to 90 parts weight, a specific common domain of 5 to 15 parts weight, and a functional common domain of 5 to 12 parts weight.

Benefits of technology

The polymer maintains excellent thermal stability and adhesion at high temperatures, avoids residual adhesive contamination, and has low pollution, and is suitable for thermal-resistant tape applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068622000001
    Figure 2025068622000001
  • Figure 2025068622000002
    Figure 2025068622000002
  • Figure 2025068622000003
    Figure 2025068622000003
Patent Text Reader

Abstract

To provide an acrylate polymer that has excellent high-temperature self-polymerization characteristics, achieves excellent heat resistance when applied on a heat-resistant tape due to its high-temperature self-polymerization characteristics without contamination of the adherends by residual adhesive, and further has a low contaminating property.SOLUTION: An acrylate polymer has a storage modulus change ratio y, calculated by the following formula (1), of 2 to 150, preferably 10 to 100. y=A / B (1). (In formula (1), y represents a storage modulus change ratio; A represents a storage modulus of the acrylate polymer when heated at 200°C for 2 hours; and B represents a storage modulus of the acrylate polymer at 23°C).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an acrylate polymer, and more particularly to an acrylate polymer having both excellent heat resistance and low staining properties. [Background technology]

[0002] Normally, pressure sensitive adhesives are in a soft solid (viscoelastic) state at temperatures around room temperature, and have the property of easily adhering to an adherend when pressure is applied. Taking advantage of such properties, pressure sensitive adhesives are widely used in various fields as substrate-attached pressure sensitive adhesive sheets in which a pressure sensitive adhesive layer is provided on a substrate, or substrate-less pressure sensitive adhesive sheets without a substrate.

[0003] Depending on the application, various properties are required for the adhesive. For example, when used in heat-resistant application fields such as heat-resistant protection or heat-resistant sealing processes, silica gel-based polymers are usually used as adhesives. However, the use of silica gel-based polymers significantly reduces the surface energy of the substrate, which reduces the success rate of wire bonding and affects performance such as sealing yield. Therefore, currently, attempts are being made to replace silica gel-based adhesives with acrylic adhesives. However, when multiple high-temperature operations are required, acrylic adhesives have insufficient high-temperature resistance and are prone to causing adhesive residue contamination on the adherend surface after use at high temperatures. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and has an object to provide an acrylate polymer which has excellent high-temperature self-polymerization properties, and which, when applied to a heat-resistant tape, can achieve excellent heat resistance without causing adhesive residue contamination on an adherend due to its high-temperature self-polymerization properties, and which also has low contamination properties. [Means for solving the problem]

[0005] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems and discovered that when a polymer is applied to a high-temperature environment, a secondary reaction occurs in the polymer, thereby sustainably improving the storage modulus of the polymer at high temperatures and increasing the cohesive strength, thereby solving the above problems and completing the present invention.

[0006] That is, the present invention is as follows. [1] An acrylate polymer having a storage elastic modulus change rate y of 2 to 150, preferably 10 to 100, calculated by the following formula (1): y = A / B (1) (In formula (1), y represents the rate of change in storage elastic modulus, A represents the storage modulus when the acrylate polymer is heated at 200° C. for 2 hours, B represents the storage modulus of the acrylate polymer at 23° C. [2] The acrylate polymer according to [1], wherein the acrylate polymer contains 70 to 90 parts by weight of a soft monomer, 5 to 15 parts by weight, preferably 5 to 10 parts by weight, of a monomer represented by the following formula (a) or formula (b), and 5 to 12 parts by weight of a functional monomer, relative to 100 parts by weight of the total monomer components of the acrylate polymer: [ka] (In formula (a), X1 represents -NH-R, where R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms; A represents a side chain containing one C=C at the end group. [ka] (In formula (b), X2 represents -NH, A represents a side chain containing one C=C at the end group. [3] The acrylate polymer according to [2], which satisfies any one of the following conditions (i) to (iii): Condition (i): The soft monomer is a (meth)acrylate monomer represented by the following formula (c) and having a glass transition temperature of −80 to −10° C. [ka] (In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms, Y represents a hydrogen atom or a methyl group. (ii) the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-(hydroxymethyl)methacrylamide, and 2-propenoic acid-2-[[(butylamino)carbonyl]oxy]ethyl; The monomer represented by the formula (b) is 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], N-[2-(2-oxoimidazolidin-1-yl) The compound includes at least one selected from the group consisting of 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)ethyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide and 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide. (iii) the functional monomer comprises a hydroxyl group-containing (meth)acrylate monomer and / or a carboxyl group-containing (meth)acrylate monomer, the hydroxyl group-containing (meth)acrylate monomer comprises at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and [4-(hydroxymethyl)cyclohexyl]methyl (meth)acrylate; The carboxy group-containing (meth)acrylate monomer includes at least one selected from the group consisting of (meth)acrylic acid, (iso)butenoic acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate, and 2-carboxypentyl (meth)acrylate. [4] The acrylate polymer according to any one of [1] to [3], which has a gel fraction of 10 to 50% measured at 23°C after heating at 150°C for 2 hours. [5] The acrylate polymer according to any one of [1] to [3], wherein the heat loss when the acrylate polymer is heated from 23°C to 200°C is 1% or less, preferably 0.6% or less. [6] The acrylate polymer according to any one of [1] to [3], wherein the acrylate polymer has a surface energy of 20 to 35 mN / m. [7] The acrylate polymer according to any one of [1] to [3], wherein the acrylate polymer has a glass transition temperature of -65 to -10°C, preferably -35 to -20°C. [8]. The rate of change in 180° peel adhesion to Cu plate (F A -F B ) / F A The absolute value of x 100 is 20% or less, preferably 10% or less, Here, F A The adhesive strength was measured after the acrylate polymer was applied to a PI substrate, dried, attached to a Cu plate, heated at 200°C for 1 hour, and left at 23°C x 50% RH for 0.5 hours. F B The acrylate polymer according to any one of [1] to [3], wherein the adhesive strength is measured after the acrylate polymer is applied to a PI substrate, dried, bonded to a Cu plate, and left at 23°C x 50% RH for 0.5 h. [9] The acrylate polymer according to any one of [1] to [3], wherein the acrylate polymer has an ultraviolet absorption peak of 0.22 abs or less in a wavelength region of 250 to 300 nm.

[10] Use of an acrylate polymer according to any one of [1] to [9] for producing an adhesive. Effect of the Invention

[0007] The acrylate polymer of the present invention has excellent high-temperature self-polymerization properties, and when applied to a heat-resistant tape, the high-temperature self-polymerization properties of the acrylate polymer enable the realization of excellent heat resistance and low contamination without causing adhesive residue contamination on the adherend. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Preferred embodiments of the present invention will be described below. Matters necessary for carrying out the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on carrying out the invention described in this specification and the common general technical knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general technical knowledge in the relevant field.

[0009] In the acrylate polymer of the present invention, the storage elastic modulus change rate y calculated by the following formula (1) is 2 to 150, and preferably 10 to 100. y = A / B (1) In formula (1), y represents the rate of change in storage modulus, A represents the storage modulus when the acrylate polymer is heated at 200°C for 2 hours, and B represents the storage modulus of the acrylate polymer at 23°C.

[0010] In the present invention, by controlling the storage modulus change rate y calculated by formula (1) within the range of 2 to 150, the obtained acrylate polymer has excellent high-temperature self-polymerization properties, and when applied to a heat-resistant tape, the high-temperature self-polymerization properties of the acrylate polymer prevent adhesive residue staining on the adherend, achieving excellent heat resistance and low staining properties, thereby achieving both excellent heat resistance and low staining properties. The storage modulus can be measured, for example, by the method described in the examples below. In some specific embodiments, the storage modulus change rate y calculated by the above formula (1) is 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, or 150.

[0011] The acrylate polymer of the present invention will be described in detail below.

[0012] In some preferred embodiments, the acrylate polymer contains 70 to 90 parts by weight of a soft monomer, 5 to 15 parts by weight, preferably 5 to 10 parts by weight, of a monomer represented by the following formula (a) or formula (b), and 5 to 12 parts by weight of a functional monomer, relative to 100 parts by weight of the total monomer components of the acrylate polymer: [ka] In formula (a), X1 represents -NH-R, where R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms; A represents a side chain containing one C=C at the end group. [ka] In formula (b), X2 represents -NH; A represents a side chain containing one C=C at the end group.

[0013] In one preferred embodiment, the soft monomer comprises an alkyl (meth)acrylate. As used herein, the term "alkyl (meth)acrylate" refers to an alkyl acrylate and / or an alkyl methacrylate.

[0014] The alkyl (meth)acrylate is preferably an alkyl (meth)acrylate having an alkyl group with 3 to 20 carbon atoms. Specific examples of the alkyl (meth)acrylate having an alkyl group with 3 to 20 carbon atoms are not particularly limited, but include, for example, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, butyl ... Examples of the alkyl (meth)acrylate include isooctyl acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2-EHA) are preferred. The alkyl (meth)acrylate may be used alone or in combination of two or more.

[0015] In some preferred embodiments, the soft monomer is preferably a (meth)acrylate monomer having a glass transition temperature of −80 to −10° C., as represented by the following formula (c). [ka] In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms; Y represents a hydrogen atom or a methyl group.

[0016] Examples of the alkyl group having 3 to 20 carbon atoms represented by Z include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, an n-hexyl group, a 2-ethylhexyl group, a heptyl group, an octyl group, an isooctyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, an octadecyl group, a nonadecyl group, and an eicosyl group.

[0017] Examples of the cycloalkyl group having 3 to 20 carbon atoms represented by Z include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclodecyl group, a cyclododecyl group, a 4-methylcyclohexyl group, and a 4-ethylcyclohexyl group.

[0018] Examples of the (meth)acrylate monomer having a glass transition temperature of −80 to −10° C., represented by formula (c), include 2-ethylhexyl acrylate (Tg: −70° C.) and n-butyl acrylate (Tg: −55° C.).

[0019] The content of the soft monomer is preferably 70 to 90 parts by mass, more preferably 75 to 89 parts by mass, based on 100 parts by weight of the total monomer components of the acrylate polymer. In some specific embodiments, the content of the soft monomer is preferably 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, or 90 parts by mass, based on 100 parts by weight of the total monomer components of the acrylate polymer. When the content of the soft monomer is within the above range, excellent adhesion can be obtained.

[0020] In the monomer represented by formula (a), X1 represents -NH-R, where R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms.

[0021] Examples of the alkyl group having 1 to 6 carbon atoms represented by R include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, and a hexyl group.

[0022] Examples of the cycloalkyl group having 3 to 20 carbon atoms represented by R include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclodecyl group, a cyclododecyl group, a 4-methylcyclohexyl group, and a 4-ethylcyclohexyl group.

[0023] The heteroatom in the heterocyclic group having 3 to 20 carbon atoms represented by R is preferably selected from N, O and / or S. In the present invention, the number of heteroatoms may be 1 or more. Examples of the heterocyclic group having 3 to 20 carbon atoms represented by R include a propiolactone group, a lactam group, a maleic anhydride group, a tetrahydrofuryl group, a furyl group, a thienyl group, a pyrrolyl group, a thiazolyl group, a pyridyl group, a pyrimidyl group, a quinolyl group, an indolyl group, and a purinyl group.

[0024] In some preferred embodiments, the monomer represented by formula (a) is preferably a monomer represented by formula (a1): [ka] In formula (a1), Ra1 represents a hydrogen atom or a methyl group, Ra2 represents an alkyl group having 1 to 6 carbon atoms or -Ra4-Ra5, Ra3 represents an alkyl group having 1 to 6 carbon atoms or a hydrogen atom, Ra4 represents an alkylene group having 1 to 6 carbon atoms, and Ra5 represents [ka] or a hydroxyl group, Ra6 represents an alkyl group having 1 to 6 carbon atoms, and Ra7 represents an alkyl group having 1 to 6 carbon atoms.

[0025] Examples of the alkyl group having 1 to 6 carbon atoms represented by Ra2 to Ra4 and Ra6 to Ra7 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, and a hexyl group.

[0026] In some preferred embodiments, the monomer represented by formula (a) is preferably a monomer represented by formula (a2): [ka] In formula (a2), Ra8 represents an alkylene group having 1 to 6 carbon atoms, and Ra9 represents an alkyl group having 1 to 6 carbon atoms.

[0027] Examples of the alkylene group having 1 to 6 carbon atoms represented by Ra8 include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, and a hexylene group.

[0028] Examples of the alkyl group having 1 to 6 carbon atoms represented by Ra9 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, and a hexyl group.

[0029] In some preferred embodiments, the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-(hydroxymethyl)methacrylamide, and 2-[[(butylamino)carbonyl]oxy]ethyl 2-propenoate.

[0030] As the monomer represented by the above formula (b), 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], N-[2-(2-oxoimidazolidin-1-yl)ethyl] Preferably, the compound contains at least one selected from the group consisting of 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)ethyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide and 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide.

[0031] The content of the monomer represented by formula (a) or formula (b) is 5 to 15 parts by mass, more preferably 5 to 10 parts by mass, based on 100 parts by weight of the total monomer components of the acrylate polymer. In some specific embodiments, the content of the monomer represented by formula (a) or formula (b) is preferably 5 parts by mass, 6 parts by mass, 7 parts by mass, 8 parts by mass, 9 parts by mass, 10 parts by mass, 11 parts by mass, 12 parts by mass, 13 parts by mass, 14 parts by mass, or 15 parts by mass, based on 100 parts by weight of the total monomer components of the acrylate polymer. When the content of the monomer represented by formula (a) or formula (b) is within the above range, the high-temperature self-polymerization properties of the acrylate polymer are improved, and excellent heat resistance is obtained.

[0032] As the functional monomer, a monomer having a polar group can be suitably used. The monomer having a polar group is useful for introducing a crosslinking point into the base polymer or for increasing the cohesive force of the base polymer. The functional monomer can be used alone or in combination of two or more kinds. Non-limiting specific examples of functional monomers include hydroxyl group-containing monomers and / or carboxyl group-containing monomers.

[0033] The content of the functional monomer is preferably 5 to 12 parts by mass, more preferably 6 to 11 parts by mass, relative to 100 parts by mass of all monomer components of the acrylate polymer. When the content of the functional monomer is within the above range, the cohesive force of the pressure-sensitive adhesive can be prevented from becoming too high, and the adhesiveness can be improved.

[0034] The hydroxyl group-containing monomer means a monomer having at least one hydroxyl group in the molecule. When the monomer component constituting the acrylate polymer contains a hydroxyl group-containing monomer, that is, when the acrylate polymer contains a monomer unit derived from a hydroxyl group-containing monomer, a secondary bond such as a hydrogen bond with the adherend is formed, so that the cohesive force of the acrylate polymer is increased, and the change in adhesive force over time can be more effectively suppressed, and the adhesive residue on the adherend after peeling is less, and the cohesive force is higher. The acrylate polymer of this embodiment may use one type of hydroxyl group-containing monomer, or may use two or more types of hydroxyl group-containing monomer. As the hydroxyl group-containing monomer, a hydroxyl group-containing (meth)acrylate monomer is preferred.

[0035] Specific examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and [4-(hydroxymethyl)cyclohexyl]methyl (meth)acrylate.

[0036] The content of the hydroxyl group-containing monomer is not particularly limited, and for example, the content of the hydroxyl group-containing monomer is 0.5 to 6 parts by mass, preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the total monomer components of the acrylate polymer. When the content of the hydroxyl group-containing monomer is within the above range, secondary bonds such as hydrogen bonds with the adherend are formed, so that the cohesive strength of the acrylate polymer is increased, and the change in adhesive strength over time can be more effectively suppressed. In addition, less adhesive remains on the adherend after peeling, and higher cohesiveness is obtained.

[0037] Carboxyl group-containing monomer means a monomer having at least one carboxyl group in the molecule. By including a carboxyl group-containing monomer in the raw material monomer of an acrylate polymer, secondary bonds such as hydrogen bonds with the adherend are formed, so that the cohesive strength of the acrylate polymer is increased, and the change in adhesive strength over time can be more effectively suppressed. In addition, less adhesive remains on the adherend after peeling, and the adhesive has higher cohesive strength. The carboxyl group-containing monomer is preferably a carboxyl group-containing (meth)acrylate monomer.

[0038] Specific examples of the carboxyl group-containing monomer include (meth)acrylic acid, (iso)butenoic acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate, and 2-carboxypentyl (meth)acrylate. The above carboxyl group-containing monomers can be used alone or in combination of two or more.

[0039] The content of the carboxyl group-containing monomer is not particularly limited, and for example, the content of the carboxyl group-containing monomer is preferably 1 to 10 parts by mass relative to 100 parts by mass of the total monomer components of the acrylate polymer. When the content of the carboxyl group-containing monomer is within the above range, secondary bonds such as hydrogen bonds with the adherend are formed, so that the cohesive force of the acrylate polymer is increased, and the change in adhesive force over time can be more effectively suppressed. In addition, less adhesive remains on the adherend after peeling, and higher cohesiveness is obtained.

[0040] The method for obtaining the acrylate polymer is not particularly limited, and various known polymerization methods such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization can be appropriately adopted. For example, the solution polymerization method can be preferably adopted. As a monomer supply method when carrying out solution polymerization, a batch injection method in which all monomer raw materials are supplied at once, a continuous supply (dropping) method, a divided supply (dropping) method, and the like can be appropriately adopted. The polymerization temperature when carrying out solution polymerization can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, and the like, and can be, for example, about 20 to 170°C (typically about 40 to 140°C).

[0041] The solvent (polymerization solvent) used in solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any one of the following solvents or a mixture of two or more of them can be used: aromatic compounds (typically aromatic hydrocarbons) such as toluene; acetate esters such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols (e.g., monohydric alcohols having 1 to 4 carbon atoms) such as isopropyl alcohol; ethers such as tert-butyl methyl ether; and ketones such as methyl ethyl ketone.

[0042] The initiator used for polymerization can be appropriately selected from conventionally known polymerization initiators according to the type of polymerization method. For example, one or more azo-based polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. Other examples of polymerization initiators include persulfates such as potassium persulfate; peroxide-based initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane-based initiators such as phenyl-substituted ethane; aromatic carbonyl compounds; and the like. Still other examples of polymerization initiators include redox-based initiators obtained by combining peroxides with reducing agents. Such polymerization initiators can be used alone or in combination of two or more. The amount of polymerization initiator used may be a normal amount, and can be selected, for example, from the range of about 0.005 parts by mass to about 1 part by mass (typically about 0.01 parts by mass to about 1 part by mass) relative to 100 parts by weight of the total monomer components.

[0043] The weight-average molecular weight (Mw) of the acrylate polymer in the technology disclosed herein is not particularly limited and may be, for example, 1,000,000 or less, and is preferably 400,000 or more. Usually, when the weight-average molecular weight Mw exceeds 1,000,000, the cohesive force tends to increase due to the effect of entanglement of the polymer, and the fluidity tends to decrease, so that a sufficient adhesive area cannot be obtained and the adherend cannot be fixed. Here, the weight average molecular weight (Mw) refers to a value calculated based on standard polystyrene obtained by gel permeation chromatography (GPC). For example, a GPC device with the model name "HLC-8320GPC" (column: TSKgelGMH-H(S), manufactured by Tosoh Corporation) can be used. In a preferred embodiment, the acrylate polymer has a gel fraction of 10 to 50% measured at 23°C after heating at 150°C for 2 hours. When the gel fraction is within the above range, excellent adhesive properties are obtained. The gel fraction can be adjusted, for example, by selecting the composition, molecular weight, etc. of the acrylate polymer. The gel fraction can be measured, for example, by the method described in the examples below.

[0044] In some preferred embodiments, the acrylate polymer has a heat loss of 1% or less, preferably 0.6% or less, when heated from 23°C to 200°C at a heating rate of 10°C / min. When the heat loss rate of the acrylate polymer is within the above range, an acrylate polymer with better heat resistance can be provided. When the acrylate polymer is used in a heat-resistant protection process, it does not increase or decrease significantly due to thermal degradation, and the cohesive force does not decrease. The loss on heating can be measured, for example, by the method described in the Examples below.

[0045] In some preferred embodiments, the surface energy of the acrylate polymer is 20 to 35 mN / m. If the surface energy of the acrylate polymer is within the above range, it is possible to provide an acrylate polymer with low staining properties. The surface energy can be measured, for example, by the method described in the Examples below.

[0046] In some preferred embodiments, the glass transition temperature (Tg) of the acrylate polymer is preferably from -65 to -10°C, more preferably from -35 to -20°C. Here, the Tg of an acrylate polymer refers to the Tg calculated by the Fox formula based on the composition of the monomer components used in the synthesis of the polymer. The Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(W i / Tg i ) In the above Fox formula, Tg is the glass transition temperature of the copolymer (unit: K), W i is the weight fraction of monomer i in the copolymer (copolymerization ratio by weight), Tg i represents the glass transition temperature (unit: K) of the homopolymer of monomer i.

[0047] The glass transition temperature of a homopolymer may be determined by the values ​​described in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989). For monomers for which multiple values ​​are described in this document, the highest value is used. If there is no description in the Polymer Handbook, the value obtained by the measurement method described in JP-A-2007-51271 is used.

[0048] In some preferred embodiments, the acrylate polymer has a 180° peel adhesion rate change (F A -F B ) / F A The absolute value of ×100 is 20% or less, preferably 10% or less. Here, F A indicates the adhesive strength measured after the acrylate polymer is applied to a PI substrate, dried, bonded to a Cu plate, heated at 200°C for 1 hour, and left at 23°C x 50% RH for 0.5 hours. F B indicates the adhesive strength measured after the acrylate polymer was applied to a PI substrate, dried, bonded to a Cu plate, and left at 23°C x 50% RH for 0.5 hours.

[0049] The rate of change in adhesive strength of acrylate polymer against Cu plate during 180° peeling (F A -F B ) / F A When the absolute value of x 100 is within the above range, excellent adhesive performance and excellent peeling workability can be imparted, the desired adhesive effect can be fully exerted during use, excellent adhesiveness can be realized, and the adhesive can be easily peeled off without causing damage to the adherend or leaving any adhesive residue stains after use. The adhesive strength can be measured, for example, by the method described in the Examples below.

[0050] In some preferred embodiments, the acrylate polymer has an ultraviolet absorption peak of 0.22 abs or less in the wavelength region of 250 to 300 nm. When the ultraviolet absorption peak in the wavelength region of 250 to 300 nm is within the above range, the side group of the monomer represented by formula (a) or formula (b) and the side group of the functional monomer form a crosslinking group. The ultraviolet absorption peak in the wavelength region of 250 to 300 nm can be measured, for example, by the method described in the Examples below.

[0051] (Application) The acrylate polymer disclosed herein is used for applications such as the production of adhesives, etc. In particular, when the acrylate polymer of the present invention is used for the production of adhesives, it can provide excellent heat resistance. EXAMPLES

[0052] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In the examples, "parts" and "%" are based on mass unless otherwise specified. In the examples, unless specific conditions are specified, the examples are performed under normal conditions or conditions recommended by the manufacturer. For materials or equipment used, unless otherwise specified, commercially available general products can be used.

[0053] <Production of Acrylate Polymer> Example 1 A reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas inlet tube and a reflux condenser was charged with 89 parts of 2-ethylhexyl acrylate (2-EHA), 2 parts of 2-hydroxyethyl acrylate (HEA), 4 parts of acrylic acid (AA), 5 parts of 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl] (WAMX), and 200 parts of ethyl acetate as a polymerization solvent. The mixture was stirred at 65°C under a nitrogen atmosphere for 1.5 hours, after which 0.3 parts of 2,2'-azobisisobutyronitrile (AIBN) was charged as a polymerization initiator and reacted at 65°C for 4 to 5 hours to obtain a solution of acrylate polymer A1.

[0054] Examples 2 to 7 Acrylate polymers A2 to A7 were produced in the same manner as acrylate polymer A1, except that the types and amounts of monomer components used were changed as shown in Table 1.

[0055] Comparative Examples 1 to 4 Except for changing the types and amounts of monomer components as shown in Table 2, acrylate polymers C1 to C4 were produced in the same manner as acrylate polymer A1.

[0056] [Table 1]

[0057] [Table 2]

[0058] <Preparation of adhesive sheet> Example 8 To the solution of the acrylic polymer A1 obtained in Example 1 above, 10 parts of ethyl acetate was added per 100 parts of the acrylate polymer A1 contained in the solution, and mixed uniformly to prepare a pressure-sensitive adhesive composition B1. The adhesive composition B1 was applied to one side of a 25 μm thick PI film serving as a base layer, and then heated at 120° C. for 3 minutes to form an adhesive layer having a thickness of 8 μm. A PET release film was then attached to the adhesive layer. The evaluation results are shown in Table 3.

[0059] Example 9 To the solution of acrylate polymer A2 obtained in Example 2 above, 10 parts of ethyl acetate was added per 100 parts of acrylate polymer A2 contained in the solution, and mixed uniformly to prepare a pressure-sensitive adhesive composition B2. The adhesive composition B2 was applied to one side of a 25 μm thick PI film that served as a base layer, and then heated at 120° C. for 3 minutes to form an adhesive layer with a thickness of 8 μm. In this way, an adhesive sheet was obtained. The evaluation results are shown in Table 3.

[0060] Examples 10 to 14 A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 9, except that the type of acrylate polymer was changed as shown in Table 3. The evaluation results are shown in Table 3.

[0061] Comparative Examples 5 to 8 A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 9, except that the type of acrylate polymer was changed as shown in Table 4. The evaluation results are shown in Table 4.

[0062] [Table 3]

[0063] [Table 4]

[0064] <Evaluation test> (1) Storage modulus change rate Measurement equipment: Waters Corporation, rheometer model: ARES G2; Measurement conditions: the angular frequency was fixed at 6.28 rad / s, the temperature was kept constant at 250°C for 2 hours, and the vibration strain was 4.98%. Specifically, the acrylate polymers of the Examples and Comparative Examples were used to prepare pressure-sensitive adhesive layers (thickness: 50 μm) for measurement. The pressure-sensitive adhesive layers were then punched out to a diameter of 7.9 mm and fixed between parallel plates, and the samples thus obtained were used as measurement samples. The storage modulus of the measurement samples was measured using a measurement device (rheometer model number: ARES G2, manufactured by Waters Corporation) when heated at 23° C. and 200° C. for 2 hours under the above conditions. The results are shown in Tables 1 and 2.

[0065] (2) Gel fraction The naturally dried acrylic polymer was heated in an oven at 150°C for 2h, and a sample weighing m1 (0.5-1.0g) was placed in a 50mL glass bottle and soaked in toluene for 1 week. After filtering the soaked mixture with filter paper (product name: NTF-1122), the remaining residue was dried at 120°C and weighed to be m2. Gel fraction = (m1-m2) / m1*100%

[0066] (3)Heating loss Measurement equipment: Waters Corporation, Thermogravimetric analyzer model: TGA550; Measurement conditions: Under a nitrogen atmosphere, the temperature was raised from 23°C to 200°C at a heating rate of 10°C / min, and the heat loss was measured when the temperature reached 200°C. The heating rate was 10°C / min, the temperature was constant at 240.0 min, and the mass flow rate was 200mL / min.

[0067] (4) Surface energy The test liquid is distilled water. Measurement device: KRUSS contact angle meter model DSA100 Specifically, the acrylate polymer was uniformly applied to a SUS403BA plate to a thickness of 8 μm, and then dried for 3 minutes at 120° C. In an environment of 23° C. and 50% RH, the measurement sample plate prepared above was placed on the measurement stage of a contact angle meter, and a test liquid was dropped onto the polymer surface to measure the surface energy.

[0068] (5) Glass transition temperature Measurement equipment: Manufacturer: PerkinElmer, Differential Scanning Calorimeter Model: DSC8000 Specifically, the acrylate polymer was naturally dried, and about 0.1 g of the polymer was placed in a DSC measurement pan to measure the glass transition temperature. Measurement conditions: under a nitrogen atmosphere, the temperature was raised from -70°C to 200°C at a heating rate of 10°C / min.

[0069] (6) Adhesive force F A The pressure-sensitive adhesive sheets prepared in each of the Examples and Comparative Examples were used as test sheets. Under standard conditions of 23°C and 50% RH, the release liner covering the adhesive surface of each test sheet was peeled off, and the exposed adhesive surface was pressed against an adherend (Cu plate) by rolling a 2 kg roller back and forth once, and then placed in an oven at 200°C and heated for 1 hour. The test sheet thus pressed against the adherend was then left for 30 minutes under the above-mentioned standard conditions, after which it was peeled off at a tensile speed of 300 mm / min and a peel angle of 180° using a tensile testing machine (manufactured by Shimadzu Corporation, product name "Tensilon") in accordance with JIS Z 0237, and the force required for the peel (180° peel adhesion) (N / 20 mm) was measured.

[0070] (7) Adhesive force F B The pressure-sensitive adhesive sheets prepared in each of the Examples and Comparative Examples were used as test sheets. In a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test sheet was peeled off, and the exposed adhesive surface was pressed against an adherend (Cu plate) by rolling a 2 kg roller back and forth once. The test sheet thus pressed against the adherend was left for 30 minutes in the above-mentioned standard environment, and then peeled at a tensile speed of 300 mm / min and a peel angle of 180° using a tensile tester (manufactured by Shimadzu Corporation, product name "Tensilon") in accordance with JIS Z0237, and the force required for the peeling (180° peel adhesive strength) (N / 20 mm) was measured.

[0071] (8) Top of ultraviolet absorption peak Sample treatment: 1 g of acrylate polymer was immersed in 30 mL of alcohol for 36 h, and the mixture of alcohol and leachate was measured under the following conditions: Measurement equipment: UV-Visible spectrophotometer, model number U-3900, manufacturer HITACHI Measurement mode: Wavelength scanning Data mode:Abs Starting wavelength: 800.00 nm End wavelength: 190.00 nm Scan speed: 300 nm / min Sampling interval: 1.00 nm

[0072] (9) Pollution The pressure-sensitive adhesive sheets prepared in each of the Examples and Comparative Examples were used as test sheets. Under standard conditions of 23°C and 50% RH, the release liner covering the adhesive surface of each test sheet was peeled off, and the exposed adhesive surface was pressed against a C26000 copper plate by rolling a 2 kg roller back and forth once, and then placed in an oven at 200°C and heated for 1 hour. The test sheet thus pressed against the adherend was then left for 30 minutes under the above-mentioned standard conditions, after which it was peeled off at a tensile speed of 300 mm / min and a peel angle of 180° using a tensile tester (manufactured by Shimadzu Corporation, product name "Tensilon") in accordance with JIS Z 0237, and the state of adhesive residue on the adherend was observed and evaluated according to the following criteria. ○: No adhesive residue △: The adhesive residue area is more than 0 and less than 10%. ×: Adhesive residue area is 10% or more

[0073] (10) Warping degree at high temperatures The pressure-sensitive adhesive sheets prepared in each of the Examples and Comparative Examples were used as test sheets. In a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test sheet was peeled off and the sheet was attached flat to the tip of an A-type copper pole (copper pole made of C26000 material, tip angle 120°). The copper pole was heated to 260°C and maintained for 3 minutes, and the warping of the adhesive sheet was visually observed and evaluated according to the following criteria. ○: No warping △: Warpage area is more than 0 and less than 10% ×: Warpage area is 10% or more

[0074] (11) Constant Load Using a commercially available double-sided tape, one side of the tape was attached to a C26000 copper plate washed with toluene as an adherend. One adhesive sheet was attached to the side of the double-sided tape opposite to the copper plate. Another adhesive sheet was cut out and attached with the adhesive layer surfaces of the two adhesive sheets aligned, with an attachment area of ​​20 mm x 100 mm. A 400 g weight was hung on one side of the other adhesive sheet, and the sheet was left at 23°C x 50 RH% for 24 hours, and the amount of separation of the aligned and attached area was measured. ◎: The separation amount of the aligned and bonded regions is less than 40 mm ◯: The separation amount of the aligned and bonded regions is 40 to 80 mm. ×: The separation amount of the aligned and bonded regions is more than 80 mm.

[0075] (12) Overall rating Based on the above evaluation results, a comprehensive evaluation was made according to the following criteria. ○: All evaluation items are rated as "○" △: There are no "x"s in the evaluation items, but there is at least one "△" ×: There is one or more "×" in the evaluation item

[0076] As is clear from Tables 1 and 3, the adhesive sheets produced using the acrylate polymers of Examples 1 to 7 had excellent evaluation results for the degree of warping at high temperatures, had excellent high temperature resistance, did not cause adhesive residue contamination on the adherend, and also had low contamination properties.

[0077] As is clear from Tables 2 and 4, the pressure-sensitive adhesive sheets produced using the acrylate polymers of Comparative Examples 1 to 4 had poor evaluation results for high-temperature warpage, did not satisfy the requirements for high-temperature resistance, and also suffered from adhesive residue contamination. [Industrial Applicability]

[0078] The acrylate polymer of the present invention has excellent high-temperature self-polymerization properties, and when applied to a heat-resistant tape, the high-temperature self-polymerization properties of the acrylate polymer enable the realization of excellent heat resistance and low contamination without causing adhesive residue contamination on the adherend.

Claims

1. An acrylate polymer, characterized in that the storage elastic modulus change rate y calculated by the following formula (1) is 2 to 150, preferably 10 to 100: y = A / B (1) (In formula (1), y represents the rate of change in storage elastic modulus, A represents the storage modulus when the acrylate polymer is heated at 200° C. for 2 hours, B represents the storage modulus of the acrylate polymer at 23°C.

2. The acrylate polymer according to claim 1, characterized in that the acrylate polymer contains 70 to 90 parts by weight of a soft monomer, 5 to 15 parts by weight, preferably 5 to 10 parts by weight, of a monomer represented by the following formula (a) or formula (b), and 5 to 12 parts by weight of a functional monomer, based on 100 parts by weight of the total monomer components of the acrylate polymer: 【Chemistry 1】 (In formula (a), X 1 represents -NH-R, where R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms; A represents a side chain containing one C=C at the end. 【Chemistry 2】 (In formula (b), X 2 represents -NH, A represents a side chain containing one C=C at the end.

3. 3. The acrylate polymer according to claim 2, wherein the acrylate polymer satisfies any one of the following conditions (i) to (iii): Condition (i): The soft monomer is a (meth)acrylate monomer represented by the following formula (c) and having a glass transition temperature of −80 to −10° C.: 【Chemistry 3】 In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms; Y represents a hydrogen atom or a methyl group. (ii) the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-(hydroxymethyl)methacrylamide, and 2-propenoic acid 2-[[(butylamino)carbonyl]oxy]ethyl; The monomer represented by the formula (b) is 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], N-[2-(2-oxoimidazolidin-1-yl) ethyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)ethyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide and 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide; (iii) the functional monomer comprises a hydroxyl group-containing (meth)acrylate monomer and / or a carboxyl group-containing (meth)acrylate monomer, the hydroxyl group-containing (meth)acrylate monomer comprises at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and [4-(hydroxymethyl)cyclohexyl]methyl (meth)acrylate; The carboxy group-containing (meth)acrylate monomer includes at least one selected from the group consisting of (meth)acrylic acid, (iso)butenoic acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate, and 2-carboxypentyl (meth)acrylate.

4. The acrylate polymer according to any one of claims 1 to 3, characterized in that the acrylate polymer has a gel fraction of 10 to 50% measured at 23°C after heating at 150°C for 2 hours.

5. 4. The acrylate polymer according to claim 1, wherein the acrylate polymer has a heat loss of 1% or less, preferably 0.6% or less, when heated from 23° C. to 200° C.

6. 4. The acrylate polymer according to claim 1, characterized in that the surface energy of the acrylate polymer is between 20 and 35 mN / m.

7. 4. The acrylate polymer according to claim 1, characterized in that the glass transition temperature of the acrylate polymer is between -65 and -10°C, preferably between -35 and -20°C.

8. Change in 180° peel adhesion to Cu plate (F A -F B ) / F A The absolute value of x100 is 20% or less, preferably 10% or less, Here, F A The adhesive strength was measured after the acrylate polymer was applied to a PI substrate, dried, attached to a Cu plate, heated at 200°C for 1 hour, and left at 23°C x 50% RH for 0.5 hours. F B The acrylate polymer according to any one of claims 1 to 3, characterized in that the adhesive strength is measured after the acrylate polymer is applied to a PI substrate, dried, bonded to a Cu plate, and left to stand at 23°C x 50% RH for 0.5 h.

9. The acrylate polymer according to any one of claims 1 to 3, characterized in that the acrylate polymer has an ultraviolet absorption peak of 0.22 abs or less in the wavelength region of 250 to 300 nm.

10. Use of the acrylate polymer according to any one of claims 1 to 9 for producing an adhesive.